Initiating buprenorphine to treat opioid use disorder without prerequisite withdrawal: an updated systematic review - Kathleen K. Adams; Kristin Waters; Diana M. Sobieraj (Addiction Science & Clinical Practice)
Abstract Background Withdrawal prior to buprenorphine initiation may be intolerable or create barriers to therapy. We aim to update our previous systematic review on the efficacy and safety of buprenorphine initiation strategies that aim to omit prerequisite opioid withdrawal (POW). Methods We used the same search strategy for this update as in the original review with the modification of an additional term “low dose.” We searched Embase and Scopus from April 11, 2020 to August 1, 2024 with searches in Google Scholar and www.clinicaltrials.gov . A study was included if it described patients with opioid use disorder or chronic pain that transitioned from a full mu-opioid agonist to buprenorphine without preceding withdrawal and reported withdrawal during initiation as an outcome. Two investigators independently screened citations and articles for inclusion, collected data using a standardized data collection tool, and assessed study risk of bias. Results Forty-four articles met our inclusion criteria; 31 were case reports/series reporting 84 cases and 13 were single-arm observational studies reporting a total of 576 cases. These studies were added to the literature from our original systematic review, totaling 59 studies and 682 patients. Sublingual buprenorphine was the most common initial formulation, comprising 55% (376/682) of cases. In case reports/series, use of a validated scale to measure withdrawal was uncommon; validated scales were only used in 36% of patients. All other patients had withdrawal assessed in a manner not utilizing a validated scale. Approximately half of these patients experienced any level of withdrawal (57/106 = 54%). The specific outcome of “any level of withdrawal” was not consistently reported in single-arm observational studies. Eight studies reported on any level of withdrawal, which occurred in 41% (177/428) of initiation attempts; some patients experienced more than one initiation attempt. Thirteen patients in case reports/series and 37 patients in the single-arm observational studies reported clinically significant withdrawal (50/682 = 7%). 81% (451/555) of patients transitioned to buprenorphine. Conclusion The prevalence of buprenorphine dosing strategies that aim to omit POW has vastly increased over the past 4 years. While quality of evidence remains low, the increased quantity of publications and integration into health-system guidelines and protocols demonstrates the need for prospective, controlled studies. It is unknown how selection bias impacts current findings, further highlighting the need for prospective, randomized, controlled trials evaluating these dosing strategies.